Wither black theology of liberation? Perspectives from the late Professor Vuyani Vellem - Pillay, Jerry (HTS teologiese studies, 2020)
The future of a black theology of liberation (BTL) has been in question since the demise of apartheid in South Africa. The constitution of democracy in the country has raised questions about the relevance and purpose of such a theology in the wake of a new dispensation. Can we continue to promote the idea of ‘blackness’ in a democratic South Africa? Extracting from the contributions of the late Professor Vuyani Vellem, and as a tribute to his work, this article aims to show that BTL definitely has a valid role for relevance and continuity. The author conducts a literature review of the material produced by Vuyani Vellem and identifies the emerging trends in which BTL continues to be alive and relevant.Contribution: The scholarly contribution of this article is its focus on the systematic and practical reflection, within a paradigm in which the intersection of religious studies, social sciences and humanities generate an interdisciplinary contested discourse.